ORGANIZATIONAL COMMITMENT OF THE EMPLOYEES IN THE OFFICE OF THE NATIONAL WATER RESOURCES - Sasang, Duanpen; โกวงศ์ ศรีรัฐ (Thai Interdisciplinary and Sustainability Review, 2023)
The objectives of the research were to study the level of organizational commitment of the employees in the Office of the National Water Resources (ONWR), to compare the organizational commitment of the employees in the ONWR according to the demographic factors and to study the relationship between quality of working life factor and the organizational commitment of the employees in the ONWR. The sample was 160 employees in the Office of the National Water Resources’ headquarter. Data were collected by questionnaires. The statistics employed in this research were frequency, percentage, mean, standard deviation, t-test, One Way ANOVA and LSD, and Pearson Product Moment Correlation Coefficient. The statistical significance was set at .05. The results revealed that the level of organizational commitment of employees in ONWR was high (mean = 3.83, S.D. = .40). The hypothesis testing showed that the differences in age and duration differently affected the organizational commitment of employees in the ONWR. In addition, the quality of working life factor had moderate positive relationship with the organizational commitment of employees in ONWR (r = .69).